A new ent-kaurane diterpenoid from the pericarps of Datura metel. Issue 9 (2nd September 2022) - Liu, Yan; Wu, Dan-Dan; Zhou, Yong-Qiang; Wu, Jia-Tong; Qi, Zi-Tang; Algradi, Adnan Mohammed; Pan, Juan; Guan, Wei; Yang, Bing-You; Kuang, Hai-Xue
Abstract: A new ent-kaurane diterpenoid, named kaurane daturoside A (1 ), was isolated from the 70%-EtOH extract of dried pericarps of Datura metel L., along with six known terpenoids, 16 α, 17-dihydroxy-ent-kauran-19-diglycoside (2 ), cyclosieversioside F (3 ), astragaloside II (4 ), ginsenoside Rg1 (5 ), astrojanoside A (6 ), celerioside E (7 ). The isolated structures were elucidated by means of spectroscopic analyses, and the compounds 2, 3, 7 were separated from Solanaceae for the first time. Meanwhile, among isolates, compounds 2 and 5 exhibited anti-inflammatory activities against LPS-activated RAW264.7 cells (IC50 <11.00 μ M). Graphical Abstract: UF0001